DEVELOPMENT OF SOFTWARE “PRODSP-1.0” FOR OPTIMIZATION OF THE DEPHOSPHORIZATION PROCESSES IN ARC STEEL-FURNACES FOR TECHNOLOGICAL LINE-UP OF RUP “BMZ” - A. A. Chichko; V. F. Sobolev; A. N. Chichko; S. G. Lihouzov; S. V. Terletskij (Литьë и металлургия)
The software “ProDSP-1,0” allowing to forecast the dynamics of the dephosphorizaiton process at casting course in arc steel-furnace, is worked out. The examples of working of different program operating regimes, showing the possibilities of phosphorus control in steel-furnace of RUP ‘'BMZ'' are given.